Refinement and Experimental Validation of a Vacancy Model of Pore Annihilation in Single‐Crystal Nickel‐Base Superalloys during Hot Isostatic Pressing. Issue 7 (3rd May 2021) - Epishin, Alexander; Camin, Bettina; Hansen, Lennart; Heuser, Marek; Lopez-Galilea, Inmaculada; Ruttert, Benjamin; Theisen, Werner; Fedelich, Bernard
Abstract : Initially, as‐cast and homogenized single crystals of nickel‐base superalloy CMSX‐4 are subjected to hot isostatic pressing at 1288 °C. Two series of experiments are conducted: under the same pressure of 103 MPa but with different durations, between 0.5 and 6 h, and under different pressures, between 15 and 150 MPa, but for the same time of 0.5 h. The porosity annihilation is investigated metallographically and by high‐resolution synchrotron X‐ray tomography. The obtained experimental results are compared with the predictions of the vacancy model proposed recently in the group. Herein, the model is further refined by coupling with X‐ray tomography. The model describes the evolution of the pore arrays enclosed in the 3D synchrotron tomograms during hot isostatic pressing and properly predicts the time and stress dependences of the pore annihilation kinetics. The validated model and the obtained experimental results are used for selecting the optimal technological parameters such as applied pressure and processing time. Abstract : Nickel‐base superalloy CMSX‐4 is subjected to hot isostatic pressing (HIP) at constant temperature with varying pressure, respectively, durations. Porosity annihilation is investigated metallographically and by high‐resolution synchrotron X‐ray computer tomography (XCT). A vacancy model describes the pore evolution during HIP predicting time and stress dependences of pore annihilation kinetics. The results are used for selecting optimal technological parameters.